2018
DOI: 10.1109/tmc.2017.2737422
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Network Coding with IEEE 802.11 DCF in Multi-Hop Wireless Networks

Abstract: Abstract-Network coding is an effective idea to boost the capacity of wireless networks, and a variety of studies have explored its advantages in different scenarios. However, there is not much analytical study on throughput and end-to-end delay of network coding in multi-hop wireless networks considering the specifications of IEEE 802.11 Distributed Coordination Function. In this paper, we utilize queuing theory to propose an analytical framework for bidirectional unicast flows in multi-hop wireless mesh netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…The proposed work concludes that the symmetric delay in packet arrival leads to an infinite packet delay. Kafaie et al [14,15] presented an analytical concept to find the network coding to improve the end-to-end delay and throughput. The authors found multi-class packet flows, which are native and coded packets.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed work concludes that the symmetric delay in packet arrival leads to an infinite packet delay. Kafaie et al [14,15] presented an analytical concept to find the network coding to improve the end-to-end delay and throughput. The authors found multi-class packet flows, which are native and coded packets.…”
Section: Related Workmentioning
confidence: 99%
“…Wireless interference caused by concurrent transmissions in different cells is mitigated by requiring devices in neighboring cells to transmit over orthogonal frequency bands. At the beginning of each time slot, all devices in the same cell compete for access to wireless media by employing the IEEE 802.11 DCF mechanism [41]. Under such a MAC scheme, the probabilities that a device executes the Source-to-Destination, Source-to-Relay, and Relay-to-Destination operations in a time slot are determined as follows (see Appendix C for the details):…”
Section: A Simulation Settingsmentioning
confidence: 99%
“…This approach provides more coding opportunities, and simplifies estimating the rate of coding opportunities at each node [88]. However, not applying opportunistic coding causes a longer end-to-end delay, especially with the asymmetric flows as the transmission of native packets should be held, waiting for coding partners to arrive.…”
Section: H Opportunistic Codingmentioning
confidence: 99%